Effect of Application Time and Dosage of Cow Manure on the Growth and Yield of Mustard (Brassica juncea L.). - Adriani, Helda Syahfari . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2017)
The aims of research were to study the effect of application time and dosage of cowmanure and their interaction on the growth and yield of mustard, as well as to find out the proper time and dosage for the best growth and yield of mustard.The research was conducted for  three months, starting from March until May 2016.  It carried out  in Muara Pahu sub district of West Kutai District. The experimental design used a randomized block design (RBD) with two factors and three replications. The first factor was the timing of cow manure application (W), consisting of three levels, namely: 5 days before planting (w1), 10 days before planting (w2), and 15 days before planting (w2).The second factor was the dosage of cow manure (K), consists of three levels,namely: 5 t/ha, equivalent to 720 g/plot (k1), 10 t/ha, equivalent to 1,440 g/plot (k2); and 15 t/ha, equivalent to 2,160 g/plot (k3).The research results showed that the application time of cow manure do not significantly affect on the plant height at 14 days after planting and number of leaves at 14 days after planting.  It affected significantly on the plant height at 21 days after planting, leaf number at 21- and 28- days after planting, and plant weight per sample plots. It affected very significantly on the plant height at 28 days after planting and the plant fresh weight per hectare.  The highest plant fresh weight was attained in the w3treatment (the application time 15 days after planting) with 27.48 t/ha, but the lowest one was found in the w1treatment (5 days after planting) with only 20.86 t/ha.Meanwhile, the cow manure dosage treatment did notaffect significantly on the plant height at 14 days after planting and number of leaves at 14 days after planting.  But it affected significantly on the plant height at 21 days after planting. And it affected very significantly on the plant height at 28 days after planting, leaf number at 21 days after planting, the fresh weight per sample plots and fresh weight per hectare.  The highest plant fresh weight was attained in the k3 treatment (dosage of cow manure 15 t/ha)with 28.72 t/ha, but the lowest one was found in the k1 treatment (5 t/ha) with only 20.84 t/ha.The interaction treatment had no significant effect on the plant height at 14-, 21- and 28- days after planting, leaf number at 14-, 21- and 28- days after planting, plant fresh weight per sample plots and fresh weight per hectare.